2009
DOI: 10.3989/collectbot.2008.v28.003
|View full text |Cite
|
Sign up to set email alerts
|

Two additions to the <i>Jacea-Lepteranthus</i> complex: parallel adaptation in the enigmatic species <i>Centaurea subtilis</i> and <i>C. exarata</i>

Abstract: Centaurea subtilis from south east Italy and C. exarata from south west Iberia were classifi ed in the AcrolophusPhalolepis group and therein in section Maculosae. A molecular survey based on ITS sequence data indicates that both species should rather be placed in the Jacea-Lepteranthus group instead. This placement is consistent with the chromosome number of the two species, which is x = 11 like the rest of species of the Jacea-Lepteranthus group, and differs from the x = 9 of the other taxa included in sect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The suitability of retaining sect. Nigrescentes as an independent group will be addressed in future studies on the basis of new molecular evidence; however, as was demonstrated in previous studies of Centaurea, the number of sections in Dostál's revision was inflated (Garcia-Jacas & al, 2006;Mameli, 2008;Hilpold & al., 2009). antennata, C. caballeroi, and C. linifolia as a single species on account of their morphological similarity (Bolòs & Vigo, 1996).…”
Section: Induratamentioning
confidence: 94%
“…The suitability of retaining sect. Nigrescentes as an independent group will be addressed in future studies on the basis of new molecular evidence; however, as was demonstrated in previous studies of Centaurea, the number of sections in Dostál's revision was inflated (Garcia-Jacas & al, 2006;Mameli, 2008;Hilpold & al., 2009). antennata, C. caballeroi, and C. linifolia as a single species on account of their morphological similarity (Bolòs & Vigo, 1996).…”
Section: Induratamentioning
confidence: 94%
“…Centaurea subtilis Bertol. was not included, as it belongs to the Jacea-Lepteranthus clade (Hilpold & al., 2009) rather than to the C. cineraria group. Voucher specimens were determined based on Pottier-Alapetite (1981), Pignatti (1982), Breitwieser & Podlech (1986), Turland & Chilton (2000), Arrigoni (2003), and .…”
Section: Methodsmentioning
confidence: 99%
“…Phalolepis and sect. Willkommia to create the molecularly defined, monophyletic "Acrolophus subgroup" of the "Jacea group" (Garcia-Jacas & al., 2006;Suárez-Santiago & al., 2007b;Hilpold & al., 2009). The Jacea group was suggested to have originated in the late Miocene in the eastern Mediterranean (Suárez-Santiago & al., 2007b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have argued that the rate of formation of fertile/viable hybrids between distantly related species should be lower than that between more closely related species (Schranz et al 2005). Centaurea horrida and C. filiformis belong to the Acrolophus subgroup of the genus (Susanna and Garcia-Jacas 2007;Hilpold et al 2009). According to Suárez-Santiago et al (2007a), its distribution is mainly restricted to the two ends of the Mediterranean Basin, with a group of species restricted to the western Mediterranean (species of the section Willkommia and several taxa of the Acrolophus-Phalolepis complex), and another group in the eastern Mediterranean (species of the Acrolophus-Phalolepis complex).…”
Section: Hybridization Between Sardinian Centaurea Species In the Evomentioning
confidence: 99%